2015
DOI: 10.4236/nr.2015.65030
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Dry Forest Products to Household Income and Determinants of Forest Income Levels in the Northwestern and Southern Lowlands of Ethiopia

Abstract: Dry forests are dominant vegetation types in East Africa. The contribution of these resources to local livelihoods is poorly understood. This study was conducted to quantify the contribution of dry forest products to household income and to identify factors that influence forest income level in the northwestern and southern lowlands of Ethiopia. Data was collected using key informant interviews, focus group discussions and formal survey administered to 428 randomly selected households from representative distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…The contribution of the total income of forest products to the total household income (Figure 2) is relatively low when compared with that found in other studies, which reported that the NTFPs contributed significantly to the total household income in Ethiopia [45], Nepal [46], and China [47]. Similar to other studies, the contribution from forest income to total income was found to be highest in HHs under the low-income group [38,48].…”
Section: People's Dependence On Forest Productssupporting
confidence: 53%
See 1 more Smart Citation
“…The contribution of the total income of forest products to the total household income (Figure 2) is relatively low when compared with that found in other studies, which reported that the NTFPs contributed significantly to the total household income in Ethiopia [45], Nepal [46], and China [47]. Similar to other studies, the contribution from forest income to total income was found to be highest in HHs under the low-income group [38,48].…”
Section: People's Dependence On Forest Productssupporting
confidence: 53%
“…Each of these benefits has a different relationship with people and is mediated by social structures that allow people to receive them [9,[40][41][42][43]. In this study, forest dependency is considered people's economic dependence on the forest [15,[44][45][46][47][48], specifically the forest net income and the collected varieties of forest products usually used by people to meet their basic needs such as subsistence. Ordinary least squares (OLS) regression was run to identify the influence of HH characteristics variables on the forest products.…”
Section: Forest Dependencymentioning
confidence: 99%
“…Aromatic resins are used in various industries, including pharmacology, cosmetics and perfumery, flavouring, etc. [81,82]. Aromatic resins provide significant revenues not only to households; national governments also generate a lot of hard currency in the related export trade [28].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the open-access dryland vegetation is a key source of feed for the livestock [24]. Thus, the different kinds of products provided by the woodlands and wooded grasslands of the region are important in improving livelihoods and alleviating poverty of the rural communities in a sustainable way [9,69,82,84]. Boswellia and Commiphora spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation